Research on Laser-TIG Hybrid Welding of 6061-T6 Aluminum Alloys Joint and Post Heat Treatment - Hongyang Wang; Xiaohong Liu; Liming Liu (Metals, 2020)
The 6061-T6 aluminum (Al) alloys was joined by the laser induced tungsten inert gas (TIG) hybrid welding technique. It mainly studied the influences of welding parameters, solution, and aging (STA) treatment on the microstructure and tensile properties of Al alloy hybrid welding joints. Microstructures of the joints were also analyzed by optical microscopy and transmission electron microscopy. Results showed that the laser induced arc hybrid welding source changed the microstructure of the fusion zone and heat effect zone. STA treatment effectively improved the mechanical properties of the softening area in the hybrid welding joint, whose values of the tensile strength and elongation were on average 286 MPa and 20.5%. The distribution of the reinforcement phases and dislocations distributed were more uniform, which improved the property of STA treated joint.